Inexpensive Apparatus for Fabricating Microspheres for 5-Fluorouracil Controlled Release Systems - Hanniman Denizard Cosme Barbosa; Bárbara Fernanda Figueiredo dos Santos; Albaniza Alves Tavares; Rossemberg Cardoso Barbosa; Marcus Vinícius Lia Fook; Eduardo Luis Canedo; Suédina Maria de Lima Silva (International Journal of Chemical Engineering)
The aim of this study was to develop an inexpensive apparatus for fabricating microspheres, based on chitosan, for 5-fluorouracil (5-FU) controlled release. Chitosan microspheres were prepared by precipitation method and the effects of manufacturing parameters (injection and airflow rates) on size distribution microspheres were analyzed by optical and scanning electron microscopy. The results show that the manufacturing parameters, injection and airflow rates, determine the microsphere size distribution. By modulating these parameters, it was possible to produce chitosan microspheres as small as 437 ± 44 μm and as large as 993 ± 18 μm. Chitosan microspheres loaded with 5-FU were also produced using the experimental equipment. The obtained microspheres presented 5-FU controlled release, indicating that the microspheres can be used orally, since they are capable of crossing the stomach barrier and of continuing with the process of 5-FU release.